HUBUNGAN PLAK GIGI, LAJU ALIRAN SALIVA, DAN VISKOSITAS SALIVA PADA ANAK USIA 6-9 TAHUN - Ani Subekti; Endah Aryati Ekoningtyas; Beni Benyamin (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2019)
The quality of saliva can have the effect of changingin the environment of oral cavity including teeth, composition of saliva, changes in the growth of plaqueattached to the surface of the tooth. The occurrence of plaque buildup is the beginning of several diseases of the oral cavity with caries and periodontal disease. The purpose of this study was to determine the relationship between the growth of dental plaque and salivary quality, in terms of salivary flow rate and salivary viscosity in elderly children 6-9 years. This type of research is an observational analytic with cross sectional design. The subject of this study is the amount of 70 respondents who examined the salivary flow rate and the saliva viscosity. The technique sampling is purposive sampling. Identification of dental plaque was measured by plague score, salivary flow rate and salivary viscosity were measured by Universal GC. The result showed that 62% of respondents had a plaque score with poor criteria with 57% of respondents having a stream of saliva with slow criteria and 47% of respondents having a salivary viscosity with thick criteria. The results of the analysis using Liniermaka Regression showed that there was a correlation between plaque scores and salivary flow rates with p = 0.037 and viscosity with p = 0.022.Conclusion: there was a relationship between the dental plaquescore and the salivary flow rate and salivary viscosity